Modelling of patterns in space and time: proceedings of a workshop held by the Sonderforschungsbereich 123 at Heidelberg, July 4 - 8, 1983 - Jäger, Willi; Murray, James D. (Springer, 1984)
Contraction patterns in a viscous polymer system -- Formation and evolution of spatial structures in chemotactic bacterial systems -- Pattern formation in directional solidification: the nonlinear evolution of cellular melt/solid interfaces -- Evolution of 3-D chemical waves in the BZ reaction medium -- Patterns of bifurcations in plane layers and spherical shells -- Chemotactic collapse in two dimensions -- Singular bifurcation in reaction-diffusion systems -- How chemical structure determines spatial structure in flame profiles -- An age-dependent population model with applications to microbial growth processes -- Cell traction and the generation of anatomical structure -- A hysteresis model for bacterial growth patterns -- Chaos in simple three- and four-variable chemical systems -- Spatial structures induced by chemical reactions at interfaces: survey of some possible models and computerized pattern analysis -- Dynamic patterns in excitable media -- Head regeneration in hydra: biological studies and a model -- Pattern formation in aspect -- Chemotaxis and cell aggregation -- Turing structures, periodic and chaotic regimes in coupled cells -- Digits, segments, somites — the superposition of sequential and periodic structures -- Spatial pattern formation in thin layers of NADH-solutions -- Pattern formation in precipitation processes -- On a mechanical model for morphogenesis: mesenchymal patterns -- Every multi-mode singularly perturbed solution recovers its stability — from a global bifurcation view point -- A mechanochemical model for plasmodial oscillations in physarum -- Genomic control of global features in morphogenesis -- Patterns of starvation in a distributed predator-prey system -- Global branches of one dimensional stationary solutions to Chemotaxis systems and stability -- Analytical and topological methods for reaction-diffusion equations -- Branching processes with interaction as models of cellular pattern formation -- Periodic growth phenomena in spatially organized microbial systems.
Keywords: Konferenzschrift; Mathematisches Modell; Morphogenese; Populationsdynamik; Muster